Strengthening Tacit and Explicit Multicultural Knowledge in Elementary Schools - Dike, Daniel; Parida, Lusila; Aristo, Thomas Joni Verawanto; Wangid, Muhammad Nur (Universitas Malikussaleh, 2020)
This study aims to develop tacit and explicit knowledge to strengthen the values and attitudes of multicultural education in elementary schools. This research method was used a case study design, and it held at the Elementary schools in Sintang regency, West Kalimantan. The Findings showed the similarity of understanding among school members to the concept of multicultural educational Catholic schools, public schools, and Islamic schools. Conceptually the understanding of multicultural education has not been formulated in an explicit multicultural idea. However, the awareness of multicultural values and attitudes has been patterned through an attitude of appreciation for diversity, respect for diversity, living brotherhood and unity rooted in the religious values of Christianity, Islam and the local traditions of Dayaks and Malay. Strengthening explicit and tacit knowledge in the process of education and learning to improve the pedagogy of equality and social justice at the elementary school level. This effort can be realized if classrooms are innovated into a multicultural epicenter. It is recommended that the process of socialization, internalization, and the combination of learning approaches and the use of various media, supplements, and multicultural learning modules. Those can be used to develop tacit and explicit knowledge so that multicultural education in elementary schools can be realized and rooted in the education process as one of the characteristics of elementary school education in Indonesia.